Nanogels as Antifungal‐Drug Delivery System Against Aspergillus Fumigatus. Issue 5 (26th March 2021) - Horvat, Sonja; Yu, Yidong; Manz, Hannah; Keller, Thorsten; Beilhack, Andreas; Groll, Jürgen; Albrecht, Krystyna
Abstract : Aspergillus fumigatus is the opportunistic fungus responsible for a variety of serious and often lethal diseases of immunocompromised patients, such as invasive aspergillosis, aspergilloma, and allergic bronchopulmonary aspergillosis. Therapeutic options for such fungal infections are limited due to the high toxicity of currently available drugs. Herein, the potency of nanogels (NGs) is assessed for uptake and delivery of antifungal therapeutics. Therefore, poly(glycidol)‐based NGs are prepared by surfactant‐free inverse nanoprecipitation. Uptake studies conducted with fluorescently labeled particles demonstrate internalization by fungi in their hyphal form. In addition, loading with both amphiphilic and hydrophobic fluorescent dyes as model drugs show efficient delivery of the fluorescent dyes into the fungus. Finally, particles are loaded with the antifungal drug itraconazole by soaking lyophilized NGs in the drug solution (breathing‐in method). Efficient delivery of the drug by nanoprecipitated NGs, improved fungicidal activity, and reduced side effects as compared with the drug itself are shown. Abstract : Poly(glycidol)‐based nanogels (NGs) are prepared by inverse nanoprecipitation. The antifungal drug itraconazole is loaded by soaking lyophilized NGs in the drug solution. NGs are able to internalize in fungi considerably improving drug efficacy.